"I am nothing": experiences of loss among women suffering from severe birth injuries in Tanzania - Mselle Lilian T; Moland Karen; Evjen-Olsen Bjørg; Mvungi Abu; Kohi Thecla W (BMC, 2011)
Abstract Background Despite the increased attention on maternal mortality during recent decades, which has resulted in maternal health being defined as a Millennium Development Goal (MDG), the disability and suffering from obstetric fistula remains a neglected issue in global health. Continuous leaking of urine and the physical, emotional and social suffering associated with it, has a profound impact on women's quality of life. This study seeks to explore the physical, cultural and psychological dimensions of living with obstetric fistula, and demonstrate how these experiences shape the identities of women affected by the condition. Methods A cross-sectional study with qualitative and quantitative components was used to explore the experiences of Tanzanian women living with obstetric fistula and those of their husbands. The study was conducted at the Comprehensive Community Based Rehabilitation Tanzania hospital in Dar es Salaam, Bugando Medical Centre in Mwanza, and Mpwapwa district, in Dodoma region. Conveniently selected samples of 16 women were interviewed, and 151 additional women responded to a questionnaire. In addition, 12 women affected by obstetric fistula and six husbands of these affected women participated in a focus group discussions. Data were analysed using content data analysis framework and statistical package for the social sciences (SPSS) version 15 for Microsoft windows. Results The study revealed a deep sense of loss. Loss of body control, loss of the social roles as women and wives, loss of integration in social life, and loss of dignity and self-worth were located at the core of these experiences. Conclusion The women living with obstetric fistula experience a deep sense of loss that had negative impact on their identity and quality of life. Acknowledging affected women's real-life experiences is important in order to understand the occurrence and management of obstetric fistula, as well as prospects after treatment. This knowledge will help to improve women's sense of self-worth and maintain their identity as women, wives, friends and community members. Educational programmes to empower women socially and economically and counselling of families of women living with obstetric fistula may help these women receive medical and social support that is necessary.